Cannabis use and opioid relapse: An exploratory survival analysis of prospectively collected data - Naji, Leen; Rosic, Tea; Sanger, Nitika; Dennis, Brittany; Hillmer, Alannah; Hudson, Jacqueline; Worster, Andrew; Paul, James; Marsh, David C.; Thabane, Lehana; Samaan, Zainab (Frontiers in Psychiatry, 2022)
Importance: It is known that only minority of patients with opioid use disorder (OUD) receive treatment, of which only a fraction successfully complete treatment as intended. Factors associated with poor treatment outcomes remain unclear, and there is emerging but conflicting evidence that cannabis use may mitigate opioid use. Objective: To analyze predictors of relapse amongst patients receiving buprenorphine-naloxone for OUD and identify the association between cannabis use and time to relapse Design: Data were prospectively collected between May 2018 and October 2020, and patients were followed for 12 months. Setting: Thirty-one outpatient opioid agonist treatment clinics across Ontario, Canada Participants: All patients 16 years of age or older receiving buprenorphine-naloxone for OUD who had a urine toxicology screen negative for opioids at baseline were eligible for inclusion. Of the 488 patients consecutively sampled, 466 were included. Exposure: Cannabis use Main outcome and measure: Relapse to opioid use assessed using urine toxicology screens. We employed a multivariable Cox-proportional hazard model for our analyses. Results: We found that cannabis use was not protective against relapse (hazard ratio [HR]=1.03, 95% confidence interval [CI]: 0.78, 1.36, p=0.84). We found that participants who have been in treatment for at least two years had a 44% decrease in the hazard of relapse compared to those in treatment for less than a year (HR=0.56, 95% CI: 0.34, 0.92, p=0.021). We also found that the hazard of relapse was 2.6 times higher for participants who were intravenous drug users (HR=2.61, 95% CI: 1.74, 3.91, p<0.001), and that for every 1mg increase in the participants’ buprenorphine-naloxone dose, the hazard of relapse is 2% greater (HR=1.02, 95% CI: 1.01, 1.03, p<0.001). Conclusion: Our analysis failed to show cannabis to be protective against relapse to opioid use in patients receiving buprenorphine-naloxone for OUD. We identified that individuals who inject drugs, are on higher doses of buprenorphine-naloxone, or have been in treatment for less than two years have a higher hazard for relapse. The presence of such factors may thus warrant closer patient follow-up and more stringent treatment protocols to mitigate risk of relapse and potential overdose.